Eating Defensively: The Nutrition and Food Safety Benefits of Cooked Produce - Morgan Dehnard; Amy Simonne; Gail P. Kauwell (EDIS)
Current nutrition trends such as the “raw food diet” may lead consumers to believe that raw leafy vegetables are more nutritious than cooked vegetables, despite research showing that cooked vegetables make important nutritional contributions. This publication describes the nutrient retention and quality of cooked vegetables, explains why cooking vegetables is appropriate for consumers with food safety concerns, and provides tips for preparing cooked vegetables. This 4-page fact sheet was written by Morgan Dehnard, Amy Simonne, and Gail P. A. Kauwell, and published by the UF Department of Family Youth and Community Sciences, October 2013.